Repurchase Intention pada Live Streaming Produk Thrift di Shopee: Peran Customer Trust dan Perceived Value dengan Mindfulness sebagai Moderasi - Alin Riqqoh Dini Safia; Laily Muzdalifah; Muhafidhah Novie; Afifatus Sholikhah (Riwayat: Educational Journal of History and Humanities, 2025)
The rise of digital technology has altered how consumers purchase online, as seen by the growing popularity of live streaming on e-commerce sites like Shopee. This research uses mindfulness as a moderating variable to examine how customer trust and perceived value affect repurchase intention for secondhand goods sold via Shopee Live Streaming. Purposive sampling approaches were used to pick 170 respondents for this research, which combines a quantitative approach with a survey method. Partial Least Squares (PLS) were used to evaluate the data. The study's findings show that Repurchase Intention is positively and significantly impacted by Customer Trust and Perceived Value. Additionally, Repurchase Intention is significantly impacted directly by mindfulness. However, it was not shown that mindfulness had a substantial moderating impact in the link between perceived value and repurchase intention or between customer trust and repurchase intention. This finding suggests that although consumers with high levels of trust and perceived value tend to make repeat purchases, the level of Mindfulness does not strengthen the relationship in the context of shopping via Live Streaming. This research contributes to marketers and business actors to put more emphasis on strategies that build trust and create product value in increasing consumer repurchase intentions.